Study of boundary layer effects at ply interfaces of laminated composites using homogenization theory. (15th April 2022) - Koley, S.; Upadhyay, C.S.; Mohite, P.M.
Abstract: A conventional analysis of unidirectional composite laminates is based on the use of average (or homogenized) properties, of the heterogeneous media, at the ply level. Plies with different orientations are stacked up to create the laminate. At free edges of the laminate, strong interfacial boundary layers are created, giving rise to large transverse normal and shear stresses. Away from free edges, and on other boundaries, these boundary layers are not present. In this work, possibly for the first time, the interface between the plies is studied in interior regions, away from the free edge. This is important because the effective media creates a fictitious interface, and true local stress states may be very different from that obtained from the conventional analysis, due to a breakdown of inherent asymptotic assumptions. This study proposes a new micromechanical approach to resolve inter-ply interfaces. Using this method, it is shown that interfacial boundary layer plays a significant role in the local stress state. This is demonstrated through the specific example of a cross-ply laminate.